Análise comparativa de genes das caseínas de búfalo - Naressi, Bruna Cristina Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Among milk proteins, the caseins (alpha-s1, alpha-s2, beta- and kappa-casein) play a crucial role considering their high nutritional value and physicochemical characteristics which contribute to the manufacture of dairy products. These proteins are encoded by the CSN1S1, CSN1S2, CSN2 and CSN3 genes, respectively. In order to analyze the buffalo casein genes and compare the sequences with other species, the goal of the present study was to identify, characterize and sequence clones from a buffalo genomic library. A total of 33,792 clones were evaluated, and two clones were identified as positive, one for the CSN1S1 gene (clone A/2) and other for the CSN3 gene (clone L/8). The DNA sequence from clone A/2 identified the whole CSN1S1 and a partial sequence from the CSN2 genes. The DNA sequence from clone L/8 revealed a partial sequence from the CSN3 gene. The CSN1S1 gene presented a total of 17,008 bp organized in 19 exons ranging from 24 bp to 380 bp and 18 introns ranging from 90 bp to 1,710 bp. Comparative analysis showed sequence conservation higher than 85% on exons and introns of the CSN1S1 gene when compared with the cattle gene sequence. The partial sequence from the CSN2 gene included exon 9 and part of intron 8, with conservation higher than 98% when compared with the cattle sequence. The partial sequences of the CSN3 gene included parts of the introns 2 and 3, the whole sequence of intron 4 and exons 3, 4 and 5. These sequences showed conservation higher than 94% with cattle. The identification of repetitive sequences showed that 43.83% of DNA sequence from clone A/2 and 44,98% from clone L/8 were represented by retrotransposable elements. Further comparative analysis showed buffalo specific repetitive sequences in the CSN1S1 gene and the partial CSN3 gene with when compared with other bovids species. The coding sequence of the buffalo CSN1S1 gene showed 98%, 93%, and 90% of identity with the correspondent sequences in cattle ...

Dentre as proteínas do leite, as caseínas (alfa-s1, alfa-s2, beta- e kapa-caseína) assumem papel de destaque devido ao alto valor nutritivo e às características físico-químicas que favorecem a fabricação de derivados do leite. Essas proteínas são codificadas pelos genes CSN1S1, CSN1S2, CSN2 e CSN3. A fim de realizar análise comparativa dos genes das caseínas de búfalo, o presente trabalho teve como objetivo a identificação, caracterização e sequenciamento de clones da biblioteca genômica de búfalo, visando analisar a estrutura molecular de genes das caseínas. Dentre os 33.792 clones avaliados, foram identificados dois clones positivos para genes das caseínas, um para o gene CSN1S1 (clone A/2) e outro para o gene CSN3 (clone L/8). Na sequência de DNA obtida a partir do clone A/2, foram identificados os genes CSN1S1 inteiro e CSN2 parcial, enquanto que nas sequências de DNA do clone L/8 identificou-se o gene CSN3 partial. O gene CSN1S1 apresentou 17.008 bp organizados em 19 éxons com tamanhos variando de 24 bp a 380 bp e 18 íntrons com tamanhos de 90 bp a 1.710 bp. As análises comparativas revelaram que os éxons e íntrons desse gene apresentaram conservação acima de 85% entre búfalo e boi. As porções do gene CSN2 identificadas incluíram o éxon 9 e parte do íntron 8, os quais mostraram conservação acima de 98% com as sequências correspondentes em boi. Já as sequências parciais do gene CSN3 abrangeram parte dos íntrons 2 e 3 e o íntron 4 completo, além dos éxons 3, 4 e 5. Estas sequências apresentaram conservação acima de 94% com as correspondentes em boi. As análises de identificação de sequências repetitivas mostraram que 43,83% e 44,98% das sequências de DNA do clone A/2 e L/8, respectivamente, são representadas por elementos retrotransposons. Nas análises comparativas, tanto o gene CSN1S1 quanto o gene CSN3 parcial apresentaram sequências repetitivas búfalo específicas. A sequência ...
Keywords: Bufalo; Polimorfismo (Genetica); Genes; Caseina; Genômica; Genetica animal; Casein